O TRANSBORDAMENTO DO SANGUE EM VERONICA STIGGER: IMAGEM, TEMPO E LINGUAGEM - MOTTER, FERNANDA (2019)
This dissertation aims to analyze Veronica Stigger's Sul (2016) and Os Anões (2010), from what we call blood overflow, a designation loaded of image, time and language and characterized by comic, tragic and ironic gestures. Thus, this blood, which runs through Stigger's writings, comes in many forms. In Sul (2016), gushes and runs through all the texts that make up the book, from the cover to the last page; in Os Anões (2010), is immersed in most of the short stories and and flash fictions that, in a cunning and spectacular way, produce effects and meanings in the text. This blood trickles down to Sombrio ermo turvo (2019), especially in the short story entitled “O livro”, which gives new meanings to the two publications analyzed here. In them, it is noted that the literature of Veronica Stigger, through experimentalism, transforms narratives into sensory and imaginary experiences for readers. Thus, to give theoretical-methodological support, our readings turn to Giorgio Agamben (2007; 2009; 2012) and Alberto Pucheu (2014) to discuss the notion of contemporary; Walter Benjamin (1984) in order to highlight the concepts of allegory, time and image; Georges Didi-Huberman (2018; 2017; 2015; 2012) to dialogue with aspects of image, montage and the concept of “olho-jorro”. Besides these, we highlight the works of Aguilar and Cámara (2017), which propose us to think about the body through the concept of performance; as well as the studies by Rosalind Krauss (1984), Florencia Garramuño (2014) and Natalia Brizuela (2014) on considerations around experimentalism to be an expansion of the literary.